Population-based prevalence of multiple radiographically-defined hip morphologies: the Johnston County Osteoarthritis Project - Raveendran, R; Stiller, J; Alvarez, C; Renner, J; Schwartz, T; Arden, N; Jordan, J; Nelson, A (Elsevier, 2017)
OBJECTIVE:To provide the first prevalence estimates of different radiographic hip morphologies relevant to dysplasia and femoroacetabular impingement in a well-characterized USA population-based cohort. METHODS:Cross-sectional data were from the baseline examination (1991-1997) of a large population-based prospective longitudinal cohort study (The Johnston County Osteoarthritis Project). HipMorf software (Oxford, UK) was used to assess hip morphology on anteroposterior (AP) pelvis radiographs. Weighted, sex-stratified prevalence estimates and 95% confidence intervals for four key hip morphologies (AP alpha angle, triangular index sign, lateral center edge angle (LCEA), and protrusio acetabula) were derived and further stratified by age, race and body mass index (BMI). RESULTS:A total of 5192 hips from 2596 individuals were included (31% African American, 43% male, mean age 63 years, mean BMI 29 kg/m2). Cam morphology was seen in more than 25% of men and 10% of women. Mild dysplasia was present in about 1/3 of men and women, while pincer morphology was identified in 7% of men and 10% of women. Femoral side (cam) morphologies were more common and more frequently bilateral among men, while pincer morphologies were more common in women; mixed morphologies were infrequent. African-Americans were more likely to have protrusio acetabula than whites. CONCLUSION:We report the first population-based prevalence estimates of radiographic hip morphologies relevant to femoroacetabular impingement (FAI) and dysplasia in the USA. These morphologies are very common, with ¼ men and 1/10 women having cam morphology, 1/3 of all adults having mild dysplasia, and 1/15 men and 1/10 women having pincer morphology in at least one hip.